Utilization Of Wordwall In Formative Assessment To Improve Students' Learning Outcomes In Physics Subjects - Fajaryati, Dewi; Ratnawati, Eka; Bahari, Yohanes; Warneri (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
In the era of modern education, the use of digital platforms can be designed to facilitate interactive learning and formative assessment. This study aims to examine the use of the wordwall platform in formative assessment to determine the level of learning outcomes in physics subjects. The scope of the study includes the application of digital-based formative assessment on the topic of measurement in class X. The study applies a quantitative method with a quasi-experimental approach using the Post-test Only Control Group design. The study population consisted of all 210 class X students at SMA Negeri 1 Selakau. The sample taken was 70 students consisting of two groups: 35 students from class XD as the control group and 35 students from class XE as the experimental group. The data were analyzed using parametric statistical tests to identify significant differences between the post-test results of the control group and the experimental group, which were assessed through multiple-choice questions. The results showed a significance value (2-tailed) of 0.00, which is smaller than 0.05, so there is a significant influence in the use of Wordwall media compared to Google Form. This finding identifies that Wordwall can be an effective formative assessment media in improving student learning outcomes, especially in physics subjects. Therefore, the use of Wordwall as a formative assessment media can be considered not only for physics subjects, but also for other subjects, in order to support a more interactive and efficient formative assessment process.